Literatur Review Hubungan Usia dengan Pemilihan Alat Kontrasepsi - Oksi Trijayanti; Luvi Dian Afriyani; Heni Rusmayani; Uswatun Khasanah; Andy Ulmi; Nelli Angriani (Universitas Ngudi Waluyo, 2022)
Indonesia is one of the countries with the most population in the world. Population growth in Indonesia reaches 1.49% per year. So that in 2010, the population in Indonesia reached 235.5 million people. The impact of this population explosion is the emergence of various social problems. For this reason, the government has actively implemented programs to suppress the population using contraception or the Family Planning program. Family Planning Program Reports on contraceptive use in couples of childbearing age alone showed that the use of MKJP was still low, ranging from 3-4%, where the use of injectable contraceptives was the highest at 32% and followed by the use of contraceptive pills as much as 14%. Using a literature review study containing a description of the theory, findings and other research materials obtained from reference materials to be used as the basis for research activities. The description in this literature review is directed to develop a clear framework of thinking about solving the problems that have been described previously in the formulation of the problem. the results of the study prove that there is a relationship between family planning experience and the choice of contraceptive method Abstrak Indonesia merupakan salah satu negara dengan jumlah penduduk paling banyak di dunia. Pertumbuhan penduduk di Indonesia mencapai 1,49% pertahun. Sehingga pada tahun 2010, jumlah penduduk di Indonesia mencapai 235,5 juta jiwa. Dampak dari adanya ledakan jumlah penduduk ini adalah munculnya berbagai masalah social, untuk itu, pemerintah secara aktif telah melakukan program penekanan penduduk menggunakan kontrasepsi atau program Keluarga Berencana. Program Keluarga Berencana Laporan penggunaan kontrasepsi pada Pasangan Usia Subur saja didapatkan data penggunaaan MKJP masih rendah yaitu berkisar antara 3-4%, dimana penggunaan kontrasepsi suntik adalah yang paling tinggi yaitu sebesar 32% dan diikuti penggunaan kontrasepsi Pil sebanyak 14%. Mengunakan studi literatur review berisi uraian tentang teori, temuan dan bahan penelitian lain yang diperoleh dari bahan acuan untuk dijadikan landasan kegiatan penelitian. Uraian dalam literature review ini diarahkan untuk menyusun kerangka pemikiran yang jelas tentang pemecahan masalah yang sudah diuraikan dalam sebelumnya pada perumusan masalah. Hasil penelitian membuktikan bahwa ada hubungan usia dengan pemilihan alat kontrasepsi.